2017
DOI: 10.12973/ejmste/78523
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation Based on Teachers’ and Students’ Opinions on Art Curricula in Northern and Southern Cyprus

Abstract: The purpose of this study is to make an evaluation based on opinions of teachers and students on the Year 8 visual art curricula implemented at the secondary education level in both northern and southern Cyprus schools. Ten Year 8 Visual Art teachers from Northern Cyprus (n=10) and Southern Cyprus (n=13), and 1200 students from both sides participated in this research. Opinions of teachers on the visual art curricula gathered through semi-structured interview forms whereas opinions of students gathered through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…At this point, it can be claimed that peace culture in recent years has been discussed with different approaches and opinions and that, for a democratic and humanist viewpoint of society, art education has a special place in conveying peace culture awareness to students (Lederach & Appleby, 2010). An examination of the literature shows that several studies have focused on art educaton in the conveying of peace culture to students (Miralay, 2017;Miralay & Hürsen 2016;Ishaq, 2007;Glenn, 2011). For example, Bajaja and Hantzopoulos (2016) showed that characteristics which require adherence to freedom, creativity and ethical ideals is essential in the popularization of peace culture.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, it can be claimed that peace culture in recent years has been discussed with different approaches and opinions and that, for a democratic and humanist viewpoint of society, art education has a special place in conveying peace culture awareness to students (Lederach & Appleby, 2010). An examination of the literature shows that several studies have focused on art educaton in the conveying of peace culture to students (Miralay, 2017;Miralay & Hürsen 2016;Ishaq, 2007;Glenn, 2011). For example, Bajaja and Hantzopoulos (2016) showed that characteristics which require adherence to freedom, creativity and ethical ideals is essential in the popularization of peace culture.…”
Section: Introductionmentioning
confidence: 99%